2022
DOI: 10.1159/000524572
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as a Predictor of the Functional Outcome in Patients with Intracranial Aneurysms

Abstract: <b><i>Introduction:</i></b> Radiological indicators in head computed tomography (CT) scan have emerged as tools to evaluate sarcopenia using the sectional area and thickness of the temporal muscle. They can be obtained by standardized measurements in preoperative image assessment of patients with brain aneurysms. We aimed to evaluate the association between functional outcomes after interventions for intracranial aneurysms (IAs) and temporal muscle thickness (TMT) and area (TMA), as sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A significant correlation between the temporalis muscle and the mRS was found in 49 elderly aSAH patients (>75 years) as well as in 298 aSAH patients who received endovascular coiling [ 25 , 26 ]. Rodrigues et al found a significant correlation between TMT/TMA and mRS at discharge/after 6 months in a study including 361 patients with intracranial aneurysms (199 ruptured, 162 unruptured) [ 19 ]. In contrast to these findings, our patient cohort showed no significant prognostic benefit for either TMT or TMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant correlation between the temporalis muscle and the mRS was found in 49 elderly aSAH patients (>75 years) as well as in 298 aSAH patients who received endovascular coiling [ 25 , 26 ]. Rodrigues et al found a significant correlation between TMT/TMA and mRS at discharge/after 6 months in a study including 361 patients with intracranial aneurysms (199 ruptured, 162 unruptured) [ 19 ]. In contrast to these findings, our patient cohort showed no significant prognostic benefit for either TMT or TMA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that skeletal muscle mass may be a useful prognostic marker in critically ill patients. The loss of muscle mass, known as sarcopenia, is associated with poor outcomes in various medical and surgical conditions, including brain metastasis, head and neck carcinoma, chronic subdural hemorrhage, intracranial aneurysm, stroke, and glioblastoma [ 16 , 17 , 18 , 19 , 20 , 21 ]. However, clinical diagnosis of sarcopenia, including measuring walking speed or hand strength, can be challenging to implement in aSAH patients with neurological deficits or impaired vigilance [ 22 ].…”
Section: Introductionmentioning
confidence: 99%